Sterigmatocystin Limits Plasmodium falciparum Proliferation and Transmission - Guodong Niu; Komal Kalani; Xiaohong Wang; Jun Li (MDPI AG, 2021)
As part of our drug discovery program against malaria, the Penicillium janthinellum extract was discovered to inhibit P. falciparum proliferation in blood and transmission to mosquitoes. Bioactivity-guided fractionation of P. janthinellum extraction was carried out using chromatographic techniques. We determined the activities of fractions against Plasmodium falciparum asexual stage parasite proliferation in culture and sexual stage parasite transmission to mosquitoes using standard membrane feeding assays (SMFA). One active compound was isolated. Based on mass spectrometry and nuclear magnetic resonance profiles, the compound was structurally determined to be sterigmatocystin. Sterigmatocystin inhibited P. falciparum proliferation in the blood with an IC50 of 34 µM and limited the sexual parasites to infect mosquitoes with an IC50 of 48 µM. Meanwhile, sterigmatocystin did not show any acute toxicity to human kidney cells at a concentration of 64 µM or lower. Sterigmatocystin can be used as a drug lead for malaria control and as a probe to understand molecular mechanisms of malaria transmission.